MORAL MOTIVATION AS PREDICTOR FOR ACTIVITY IN STUDENTS ORGANIZATION - Serafimovska, Eleonora; Markovikj, Marijana (Institute for Sociological, Political and Juridical Research, 2017)
Student organizations exist and should exist to protect the rights and interests of their members. Experiences show that membership in student organizations helps develop critical thinking about processes that occur in higher education institutions in the state, and wider, in society. It also influences the process of identification with the peer group, as well as encouraging the motivation to take coordinated action to realize their own rights and needs. Membership in student organizations should also affect the development of skills that imply the improvement of personal and professional self, such as moral judgment, non-violent means of communication, conflict resolution. If certain research is correct and say that more than 80% of students in Macedonia are not members of any student organization, then the situation is worrying and of course it is necessary to find suitable ways to change it. Therefore, a research team at the Institute for Sociological, Political and Juridical Research conducted a research on student organization, in particular about the ways in which students work, their attitudes and opinions about student organization, and their motivation to behave in accordance with the concepts of social justice. In the period of May 2017, 669 students from different faculties at the University “Ss. Cyril and Methodius” were examined about their views and opinions for student organization, as well as their moral motivation, or whether they are morally motivated to behave in accordance with the principles of social justice in society. The results show that students do not understand the concept of social justice and are very little aware that with their behavior they contribute to the fight for social justice. This also means that if they are not fully aware about their potential contribution in society they will not be active in the processes of student’s life and their future.
Keywords: Students organization, moral motivation, social justice, University “Ss. Cyril and Methodius”, Republic of Macedonia